Simplify:
$(5x - 3) (x + 2) - (2x + 5) (4x - 3)$

AcademicMathematicsNCERTClass 8

Given:

$(5x - 3) (x + 2) - (2x + 5) (4x - 3)$

To do:

We have to simplify the given expression.

Solution:

$(5x - 3) (x + 2) - (2x + 5) (4x - 3)=[5x (x + 2) -3 (x + 2)] - [2x (4x - 3) + 5 (4x - 3)]$

$= (5x^2 + 10x - 3x - 6) - (8x^2 - 6x + 20x -15)$

$= (5x^2 + 7x - 6) - (8x^2 + 14x - 15)$

$= 5x^2 + 7x - 6 - 8x^2 - 14x + 15$

$= 5x^2 - 8x^2 + 7x - 14x - 6 + 15$

$= -3x^2 - 7x + 9$

raja
Updated on 10-Oct-2022 13:19:30

Advertisements